AFSRE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
AFSRE, the International Association for Farming Systems Research and Extension, is an international non-profitmaking association with its Head Office in the Philippines. It comprises research workers and independent producers as well as regional...